1999
DOI: 10.1021/ma9815197
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins in Polymer Synthesis:  Free Radical Polymerization of a N-Methacryloyl-11-aminoundecanoic Acid/β-Cyclodextrin Pseudorotaxane in an Aqueous Medium

Abstract: The relatively hydrophobic monomer N-methacryloyl-11-aminoundecanoic acid (1) was incorporated as a guest into the cavity of β-cyclodextrin (β-CD) as a host, yielding the water-soluble monomer N-methacryloyl-11-aminoundecanoic acid/β-CD pseudorotaxane (2). This pseudorotaxane was polymerized radically in an aqueous medium by use of the water soluble azoinitiator 2,2‘-azobis(N,N‘-dimethylenisobutyramidine). The obtained poly(N-methacryloyl-11-aminoundecanoic acid) (3) was insoluble in water because of a nearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 20 publications
2
46
0
Order By: Relevance
“…211,212 These molecules are able to encapsulate hydrophobic molecules or hydrophobic side groups of polymer as guests into their cavities to form host/guest complexes in aqueous solution and in emulsion. 213,214 Recently, Ritter and co-workers 203 developed a new method to make a nearly water-insoluble photoinitiator (2-hydroxy-2-methyl-1-phenylpropan-1-one) water-soluble by complexation with β-cyclodextrin (Scheme 22). A comparative kinetic study of polymerization reactions initiated with both complexed and uncomplexed photoinitiator revealed a higher polymerization rate and better polymerization yield in the presence of the cyclodextrin/photoinitiator complex.…”
Section: Environmental Safety and Health Considerationsmentioning
confidence: 99%
“…211,212 These molecules are able to encapsulate hydrophobic molecules or hydrophobic side groups of polymer as guests into their cavities to form host/guest complexes in aqueous solution and in emulsion. 213,214 Recently, Ritter and co-workers 203 developed a new method to make a nearly water-insoluble photoinitiator (2-hydroxy-2-methyl-1-phenylpropan-1-one) water-soluble by complexation with β-cyclodextrin (Scheme 22). A comparative kinetic study of polymerization reactions initiated with both complexed and uncomplexed photoinitiator revealed a higher polymerization rate and better polymerization yield in the presence of the cyclodextrin/photoinitiator complex.…”
Section: Environmental Safety and Health Considerationsmentioning
confidence: 99%
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of MPMA/HPCD inclusion complex was further verified by 13 C-NMR spectra [ Fig. 2(B)], for which the detailed data are listed in Table II.…”
Section: Formation and Characterization Of Mpma/hpcd Inclusion Complexmentioning
confidence: 94%
“…23 The yield of the monomer in Scheme 1 was 72%. The 1 H-NMR and 13 C-NMR spectra of the monomer were recorded, as shown in Figure 1. The attributions are also presented in the figure, demonstrating the exact structure and high purity of the monomer.…”
Section: Synthesis and Characterization Of Mpmamentioning
confidence: 99%
See 1 more Smart Citation